Pesan Moral Dalam Film Petualangan Sherina 2 Analisis Semiotika Roland Barthes - Tiara, Wan; Rasyid, Abdul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The movie Petualangan Sherina 2, released in 2023, is a continuation of the movie Petualangan Sherina in 2000. The movie is directed by Riri Riza and produced by Mira Lesmana. The story tells the adventures of Sherina, a smart and brave girl who has grown up. Sherina, who works as a journalist, dreams of covering the World Economic Forum held in Switzerland. When she was supposed to go to Switzerland, Sherina was asked by her boss to move to Kalimantan to cover orangutan conservation. This research aims to find out the moral message in the movie The Platform. The research method used is qualitative research method with Roland Barthes semiotic analysis theory. The results of this study are the form of moral messages in the movie Petualangan Sherina 2 in the form of good morals and bad morals. The good morals contained in the movie Petualangan Sherina 2 is the concern for the conservation of orangutans. The bad morals contained in the movie are the theft of orangutans, damaging the natural ecosystem, and poor communication between friends.